1994
DOI: 10.1007/bf00867933
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor antagonist suppresses exercise-induced hypertrophy of skeletal muscle

Abstract: The physiological importance of the increase in androgen receptors in exercise-induced muscle hypertrophy was investigated in rats. Together with training rat gastrocnemius muscles by electrical stimulation every other day for 2 weeks, male rats were administered the androgen receptor antagonist, oxendolone. The androgen receptor antagonist effectively decreased the wet mass of the prostate, an androgen target organ, and did not significantly affect body mass. The increase in muscle mass induced by electrical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
1
5

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 14 publications
1
54
1
5
Order By: Relevance
“…Increased androgen receptor abundance could serve to increase the muscles' sensitivity to androgens. Androgen receptor induction may play an important role in overload-induced growth, because inhibition of androgen receptor action can partially attenuate overload-induced muscle growth in rats (26). However, the present data also support the hypothesis that androgen receptor induction is not sufficient for inducing muscle growth.…”
Section: Discussionsupporting
confidence: 72%
“…Increased androgen receptor abundance could serve to increase the muscles' sensitivity to androgens. Androgen receptor induction may play an important role in overload-induced growth, because inhibition of androgen receptor action can partially attenuate overload-induced muscle growth in rats (26). However, the present data also support the hypothesis that androgen receptor induction is not sufficient for inducing muscle growth.…”
Section: Discussionsupporting
confidence: 72%
“…This inhibitor has been used in cancer research in breast or prostate cancer (Bhattacharyya et al 2006, Auricchio et al 2008. Moreover, sex hormone receptor inhibitors have been used to investigate the molecular mechanism of sex hormone action in skeletal muscle (Inoue et al 1994). Interestingly, we show that the positive effect of testosterone on palmitate oxidation was abolished at the presence of the AR antagonist (CDX).…”
Section: Discussionmentioning
confidence: 87%
“…Previously Joubert and Tobin (56) demonstrated that testosterone treatment of rat levator ani muscle resulted in activation of quiescent satellite cells, and increased replication and the fusion of satellite cells with myofibers. In the rodent, the role of AR in exercise-induced muscle growth was proven (57), as antiandrogen significantly reduced skeletal muscle gain.…”
Section: Discussionmentioning
confidence: 99%